2009
DOI: 10.1016/j.alcohol.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced hyperactivity is associated with hypodopaminergia in the 22-TNJ ENU-mutated mouse

Abstract: Characterization of neurochemical and behavioral responses to ethanol in phenotypically distinct mouse strains can provide insight into the mechanisms of ethanol stimulant actions. Increases in striatal dopamine (DA) levels have often been linked to ethanol-induced hyperactivity. We examined the functional status of the DA system and behavioral responsiveness to ethanol, cocaine and a DA receptor agonist in an N-ethyl-N-nitrosourea (ENU)-mutagenized mouse strain, 22-TNJ, generated by the Integrative Neuroscien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…A systemic injection of 2 g/kg ethanol significantly increased extracellular levels of dopamine in the CPu of wildtype mice between 40 and 60 min following ethanol administration. These microdialysis results from the CPu are in agreement with several mouse microdialysis studies that have shown an approximate 50 – 170% increase in extracellular dopamine levels in response to a locomotor activating dose of ethanol [17, 19, 26, 28]. One important difference between the present study and those described above is that the majority of mouse microdialysis studies have evaluated ethanol-induced elevations in extracellular dopamine in the NAc (or ventral striatum) [17, 26, 28] and not the CPu (or dorsal striatum); but see [19].…”
Section: Discussionsupporting
confidence: 89%
“…A systemic injection of 2 g/kg ethanol significantly increased extracellular levels of dopamine in the CPu of wildtype mice between 40 and 60 min following ethanol administration. These microdialysis results from the CPu are in agreement with several mouse microdialysis studies that have shown an approximate 50 – 170% increase in extracellular dopamine levels in response to a locomotor activating dose of ethanol [17, 19, 26, 28]. One important difference between the present study and those described above is that the majority of mouse microdialysis studies have evaluated ethanol-induced elevations in extracellular dopamine in the NAc (or ventral striatum) [17, 26, 28] and not the CPu (or dorsal striatum); but see [19].…”
Section: Discussionsupporting
confidence: 89%
“…Increased dysbindin-1 expression in the hippocampi from ventilated patients suggests that this protein could play a role in the regulation of brain responses to critical illness and mechanical ventilation. Moreover, it has been described that enhanced DRD2 stimulation leads to hypodopaminergia (46). The long-term effects of these compensatory mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This timing was determined based on previous publications which tested animals 1-5 days after surgery (Narita et al, 2006; Ferris et al, 2014). Microdialysis probes (membrane length 2mm; CMA/Microdialysis) were inserted approximately 16 hr prior to the beginning of sample collections and extended 2 mm beyond the cannula tip to -4.55 V (Mathews et al, 2009). …”
Section: Methodsmentioning
confidence: 99%